Chorioretinal anastomosis and photodynamic therapy:a two-year follow-up study - Silva, RM (2007)
BACKGROUND: To evaluate the two-year efficacy of photodynamic therapy with Visudyne (PDT) in neovascular age-related macular degeneration (AMD) eyes with chorioretinal anastomosis (CRA). METHODS: A non-randomized, institutional, prospective study, of 28 consecutive eyes of 23 patients, with CRA, treated with PDT. Masked best corrected visual acuity (VA) and angiographic features at baseline and during the period of two years were evaluated. RESULTS: Twenty eight eyes completed one year and 19 eyes completed two years of follow-up. The number of treatments was 3 in the first year, and 0.8 in the second year. A VA loss < 3 lines occurred in 53% of the eyes, at two years. Treated eyes lost 0.5 lines in the first year and 2.4 lines in the second (p < 0.01). Recurrence with additional significant VA loss occurred in four eyes (21%) during the second year. Fourteen eyes (74%) showed no fluorescein leakage at two years. CONCLUSION: AMD eyes with chorioretinal anastomosis can benefit from PDT with Verteporfin at two years. However, during the second year significant additional VA loss occurs mainly due to recurrence. New modalities of treatment are necessary to achieve VA improvement in CRA eyes.